Limnephilidae - Küçükbasmaci, İbrahým; Canbulat, Savaş (Zenodo, 2020)
Family Limnephilidae Pseudostenophylax micraulax (McLachlan 1878b) —Range: Afghanistan, Kazakhstan, China (Tibet), Uzbekistan, Pakistan, Kashmir, India (Jammu, Kashmir, Ladak and Uttar Pradesh), Nepal, and Kyrgyzstan (Malicky 2013; Ma-licky 2017; Oláh 1994, 2010; Saini et al. 2001; Smirnova et al. 2016; Yang et al. 2005; Yang et al. 2016). Psilopterna hirsuta Martynov 1928 a—Range: Kazakhstan (Smirnova et al. 2016). Also the type country of this record is given as Kyrgyzstan (Morse 2020).

Published as part of Küçükbasmaci, İbrahým & Canbulat, Savaş, 2020, A List of the Caddisflies (Insecta: Trichoptera) from Kyrgyzstan, with a New Record (Triaenodes reuteri McLachlan 1880), pp. 113-122 in Zootaxa 4896 (1) on page 115, DOI: 10.11646/zootaxa.4896.1.6, http://zenodo.org/record/4359410
Keywords: Insecta; Arthropoda; Limnephilidae; Trichoptera; Animalia; Biodiversity; Taxonomy